Gonzalo Serrano: La querella en torno al silogismo 1605-1704. Conocimiento versus forma lógica. Bogota: Universidad Nacional de Colombia, 2006, 271 pp. - Cárdenas B., José Luis (2007)
The novelty to Serrano’s book is that it makes a survey of the quarrel on the syllogism that is not merely restricted to the logical and for-mal side of the discussion, but which also incorporates the problems that the formality of logic imposed on the philosophy of the times, showing the different proposals that sundry philosophers were compelled to develop upon deciding that the syllogism was obsolete. What was at stake was noth-ing less than the founding of a new logic, something which –it was soon made clear– would not be all that easy to find. As Leibniz says, the formal aspect is something that cannot be dismissed if what one wants is to en-sure logical cogency and the truth of the knowledge thence obtained.